FACTORS AFFECTING THE SUCCESS OF EARLY BREASTFEEDING INITIATION AT PMB NY MEGAWATI KURNIAWAN,AmKEB SUKAJAYA VILLAGE, CIBITUNG DISTRICT BEKASI REGENCY IN 2023 - SAGITA, SOFIYATI; Fatdo Wardani, Ika Kania (NHM PRESS, 2024)
Based On 2021 data, the total IMD Percentage in West Java is 2.293,73 down -1.04% ,while the average value of IMD Percentage each year is 2.290,32 in the last three years for Bekasi Regency coverage itself in 2021, the total percentage of IMD is 88,85% an increase from the previous year (Jannah, 2023). The impact of IMD for the mother, touch and suction on the mother’s breast encourages the formation of oxytocin which has an impact on contractions in the uterus so that it helps the placenta exit uterine contractions will reduce the placental area, because the uterus gets smaller and the walls increase by several cm. (Setyawati et al., 2013). The purpose of this study is to determine the factors that influence the success of Early Breastfeeding Initiation (IMD) at PMB Mrs. Megawati Kurniawan, AmKeb Sukajaya Village, Cibitung District, Bekasi Regency in 2023. The research method used is the cross sectional survey method. The analysis used is the Chi Square Test. This study used primary data from interviews and filling out questionnaires by 35 respondents from mothers who gave birth at PMB Mrs. Megawati Kurniawan, AmKeb of Sukajaya Village, Cibitung District, Bekasi Regency in 2023 with sample totaling. The techniques carried out are validity tests, reliability tests and normality tests with data analysis, namely univariate analysis and bivariate analysis.The results showed that the variables related to the success of IMD implementation at PMB Mrs. Megawati Kurniawan, AmKeb of Sukajaya Village, Cibitung District, Bekasi Regency in 2023 were attitude (p value 0.008), knowledge (p value 0.561), husband support (p value 0.128) and support of health workers (0.496).